LIMITATION OF MARINE CARRIER’S LIABILITY UNDER JORDANIAN LEGAL SYSTEM - AL-DABOUBI, DERAR (2020)
This article addresses the limitation of the marine carrier’s liability under both Jordanian Maritime Commercial Law (JMCL) 1972 and Hamburg Rules 1978 that has been ratified by Jordan in 2001. This article aims to show the incompatibility between these instruments in terms of evaluating rule for the compensation arising in the context of limitation of liability for marine carrier. Through this analysis, the author will point out the contradiction observed between the Hamburg Rules and JMCL, both of which are applicable by the Jordanian Cassation Court. Therefore, the article will clarify the legal basis on which applicability of either JMCL or Hamburg Rules can be decided, specifically with respect to the limitation of the liability of marine carrier, which has not been expressly determined in the judgments of the Jordanian Cassation Court. The paper ultimately reaches a set of results and then proposes some recommendations so as to eliminate the inconsistency between both the JMCL and the Hamburg Rules. This verb will contribute to consolidating the international commercial principle for the unification and harmonisation of international commercial rues.